The end of the world as we know it? : crisis, resistance, and the age of austerity - Shannon, Deric (AK Press, 2014)
"The End of the World as We Know It? explores the origins and effects of the capitalist crisis that began in 2008. It moves on to examine the responses of both the dispossessed and the ruling classes to the catastrophe, giving special attention to student mobilizations around the world. Weaving together a global network of stories and analyses, editor Deric Shannon creates an outline of what real and effective opposition to the forces that are destroying our lives and our planet might look like. From solidarity networks to revolutionary unionism, student strikes, and ever-new forms of state and corporate control, The End of the World as We Know It? is a guide to the future of anticapitalist struggle"--Provided by publisher